Anxiety symptoms are quantitatively and qualitatively different in dementia with Lewy bodies than in Alzheimerʼs disease in the years preceding clinical diagnosis. Issue 3 (28th November 2019) - Segers, Kurt; Benoit, Florence; Meyts, Jean‐Marie; Surquin, Murielle
Abstract : Aim: Dementia with Lewy bodies (DLB) is a common but underdiagnosed type of cognitive impairment and dementia. The current diagnostic criteria for research purposes have a high specificity but lack sensitivity. Moreover, patients who live alone are not always aware that they have core clinical features such as cognitive fluctuations, visual hallucinations, and parasomnia. Anxiety is a common and early manifestation in DLB. Methods: We matched 41 DLB patients with 41 patients with Alzheimerʼs disease (AD) according to gender, age, and cognitive status and retrospectively analyzed their files for the presence of anxiety, depression, constipation, and the core clinical features of DLB in the documented period before diagnosis. Results: Anxiety, but not depression, occurred significantly more frequently in DLB than in AD (63.4% vs 26.8%). It appears up to 4–5 years before the diagnosis of DLB and is associated with depression and living at home. Anxiety in DLB was often described as intermittent panic attacks without reason or during states of delirium; it was also severe enough to require medical treatment and inpatient or outpatient psychiatric care. It was often mistaken for a psychiatric illness or a manifestation of other common forms of dementia. Anxiety in AD seemed much milder, was often related to the patient's coping with cognitive dysfunction, and was never cited as a specific reason for medical help. The concomitant presence of anxiety with at least one core clinical criterion of DLB enabled us to differentiate it from AD in our study, with a sensitivity of 63.4% but a specificity of 100%. Conclusions: In all patients over 50 who present with cognitive problems and anxiety, DLB should be considered. Patients and informants should be carefully questioned regarding the presence of other typical signs and symptoms of DLB.